Evaluation of Mitigation Initiatives for Simultaneous Air Pollution and Municipal Solid Waste Systems: A System Dynamics Approach - Vasquez-Perez, O; Espinoza-Perez, A (Elsevier Ltd, 2024)
Numerous policies have been implemented in the global effort to achieve sustainable development and improve the population s quality of life, such as those to reduce air pollution or manage municipal solid waste (MSW). However, these policies were designed disregarding their simultaneous impact on human health and ecosystem in the same city. This study implements system dynamics methodology to simulate coexisting air pollution and MSW management systems, as well as their corresponding policies and decontamination plans, to investigate their influence on human health and ecosystem and to propose policy improvements based on the specific setting of the study. The case study corresponds to Temuco and Padre Las Casas (TPLC). Results show that TPLC requires an integrated policy approach that includes increasing the equipment replacement and advanced technologies for MSW management to achieve reductions in human health impacts by approximately 10%. © 2024 Elsevier Ltd